Optimalisasi Media Sosial sebagai Strategi Pemberdayaan Mahasiswa Muslim dalam Pengembangan Usaha Halal di Kabupaten Bojonegoro - Nanang Setiawan; Thorida Nur Asih; Aulyatu Rachmadhani Hakim; Muhammad Mujib (STAI Senori Tuban, 2026)
Although the population of young Muslims in Indonesia continues to grow, their halal literacy and understanding of Sharia-compliant business practices remain limited. At the same time, social media offers significant opportunities for developing halal businesses among Muslim millennials. The program employed a participatory action research approach within a qualitative framework. This community service program, implemented through an Entrepreneurship course at Institut Agama Islam Al-Fatimah, aimed to enhance students’ halal literacy and their capacity to utilize social media for halal business development aligned with Islamic values and Sharia-based brand identity. Using a qualitative approach, the program involved course-based assignments, mentoring, focus group discussions, observation, and literature review conducted over one academic semester. Students developed halal business ideas and applied digital marketing strategies through social media platforms. The results indicate that social media integration in Entrepreneurship learning effectively increases halal awareness, creativity, and digital skills, while enabling students to test business ideas, build brands, and reach broader markets at low cost. However, students’ understanding of halal remains stronger in marketing aspects than in substantive areas such as production processes and halal supply chains.